Exploring a framework for decolonised disability-inclusive student walk support practices in an open and distance learning institution - Sipuka, Olwethu (Division of Disability Studies, 2021)
This research examined underpinning aspects of decolonised support service needs and preferences of open distance learning students with disabilities. In order to fulfil this purpose, views and perceptions of students with disabilities on the importance, availability, and accessibility of student support services were investigated. The extensive literature review done confirms the extent to which decolonisation of higher education has received prominence however, that prominence is not given to the decolonisation of support services for students with disabilities. The Capabilities Approach is utilized as the theoretical framework for this study. It coupled with the Social Model of disability channels our focus on the person's abilities rather than the impairments. Positioned as a qualitative illustrative case study, it sought to examine the factors that positively and negatively affect increased decolonisation of the higher education experiences of students with disabilities in South African universities. As the foremost Open Distance Learning institution in South Africa; the University of South Africa is the primary site for the study. Interviews with students with disabilities, the student representative council and staff members responsible for student support revealed the current experiences and perceptions of both students and staff regarding the topic. The study findings revealed key aspects of a decolonised Student Walk as being internationally relevant, students playing a pivotal role as a stakeholder, controlling worldviews, replicating inequalities and curriculum and power plays and clear strategy as a cardinal aspect of the process. It also discovered that decolonisation was not well understood by both staff and students, hypothetically pointing to many barriers than opportunities. There was disjointed institutional support initiatives that needed to be decolonised, inclusive, teaching and student support aligned. The major implications are linked to institutional level strategic support, staff training and awareness, policy reflection and strategy, inclusive initiatives and student involvement. Above all, a decolonised Student Walk framework has been proposed.